The role of administrative actions in fighting the coronavirus pandemic in Iraq - Ali, Mohammed Noori; Nurhafilah Musa (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2022)
The objective of this article is to assess the efficacy of preventive administrative actions for the containment of the coronavirus pandemic in Iraq. In particular, the article examines the extent to which administrative authorities can strike a balance between the constitutional rights of individuals and the public interest in their fight against this pandemic. Given its law-oriented nature, this article employs a qualitative, analytic research methodology. It builds on laws, constitutions, textbooks, journals and newspaper reports, as well as official publications by governments and international bodies. Specifically, it identifies administrative decisions, laws and other measures relevant to the coronavirus pandemic and proceeds to subject them to rigorous analysis. A key finding is that administrative actions can be effective in curbing the coronavirus pandemic in Iraq. However, they have two limitations. First, is the extent to which administrative procedures are subject to the principle of legality and judicial oversight. An important question is raised as to how to reconcile administrative actions meant to protect public health with constitutional rights guaranteed in Chapter II of the Iraqi constitution of 2005. Second, the formation of various committees, which issue diverse decisions to tackle the pandemic hinders coordination and consistency in decision-making. This article concludes that administrative actions would be more effective in combatting the coronavirus pandemic, if administrative authorities in Iraq remain bound by the law. It suggests that the present health situation should not be used as a justification for the abuse of authority under the pretext of public interest. To harmonise private interests protected by the law and the state’s interest in preserving public health, administrative actions must be properly coordinated, fair and equitable. In this context, the Iraqi administrative judiciary must exercise greater oversight over the actions of administrative authorities.